GLOBECOM 2022 - 2022 IEEE Global Communications Conference 2022
DOI: 10.1109/globecom48099.2022.10001209
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Static Sensing for Near-Field RIS Localization

Abstract: We address the localization of a reconfigurable intelligent surface (RIS) for a single-input single-output multicarrier system using bi-static sensing between a fixed transmitter and a fixed receiver. Due to the deployment of RISs with a large dimension, near-field (NF) scenarios are likely to occur, especially for indoor applications, and are the focus of this work. We first derive the Cramér-Rao bounds (CRBs) on the estimation error of the RIS position and orientation and the time of arrival (TOA) for the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…We can solve the problem (24) through 1D line search or gradient-based iterative search with an initial point, which can be provided by an FFT-based method [26].…”
Section: A Bs-hris Channel Parameter Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…We can solve the problem (24) through 1D line search or gradient-based iterative search with an initial point, which can be provided by an FFT-based method [26].…”
Section: A Bs-hris Channel Parameter Estimationmentioning
confidence: 99%
“…In the second scenario, a UE can use an RIS(s) to enable its localization, where the RIS(s)'s state is unknown and needs to be estimated. This problem is known as RIS localization, which one can see as a bi-static sensing or a calibration problem [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the specific case of NF localization, many other RIS optimization schemes have been put forward, such as SNR maximization in [25] and [26] and DFT matrices in [27]. On the other hand, a traditional randomized RIS phase design was considered in [28] to achieve bi-static localization of the RIS. In [15], random profiles are also utilized and the authors showed, theoretically, that this profile design can ensure localization continuity in NLoS conditions through direct positioning out of one single RIS-reflected path, relying on NF properties.…”
Section: Related State Of the Artmentioning
confidence: 99%
“…Introducing the RIS to assist in communication-based positioning has become a research focus [32], [31]. From the perspective of mobility, the research can be divided into two categories: static positioning [17], [18], [19] and dynamic positioning [15], [13]. The former considers scenarios where the user undergoes minimal movement within a coherent time, and the latter involves scenarios with the opposite characteristic.…”
Section: Introductionmentioning
confidence: 99%